Trucidocynodon riograndensis gen. nov. et sp. nov. (Eucynodontia), a new cynodont from the Brazilian Upper Triassic (Santa Maria Formation) - de Oliveira, Téo Veiga; Soares, Marina Bento; Schultz, Cesar Leandro (Zootaxa, 2010)
An almost complete skeleton of a new carnivorous cynodont from the Upper Triassic of Southern Brazil, Trucidocynodon riograndensis gen. nov. et sp. nov., is described. The new taxon is very similar to Ecteninion lunensis Martinez et al. 1996 from Upper Triassic of Argentina (Ischigualasto Formation). Both have an elongated skull, large pterygoid flanges, a well developed orbitosphenoid, a relatively short osseous secondary palate, greatly developed canines and sectorial postcanines with posteriorly directed cusps. However, the new taxon shows some differences relative to E. lunensis such as an open pterygoparoccipital foramen, the posterior opening of the post-temporal foramen enclosed by tabular and squamosal, and upper incisors with serrated cutting edges. The more remarkable features of the postcranium of T. riograndensis are the presence of 32 presacral vertebrae, a greater number than in most of non-mammaliaform cynodonts, the accentuated lumbarisation of the posterior trunk vertebrae and a remarkable morphological gradient in the caudal vertebrae; the femur and humerus show some interesting adaptations suggesting a more upright limb posture. The overall morphology of the astragalocalcaneal complex is similar to that of Diademodon and of the therocephalian Bauria.